2014
DOI: 10.1186/1754-9493-8-2
|View full text |Cite
|
Sign up to set email alerts
|

Hospital costs associated with surgical morbidity after elective colorectal procedures: a retrospective observational cohort study in 530 patients

Abstract: BackgroundPostoperative complications contribute to morbidity and mortality. This study assessed the impact of surgical complications on healthcare resource utilization for patients undergoing elective colorectal procedures.MethodData were obtained on 530 consecutive colorectal operations performed from January 2010 to January 2011. Patient demographics, type of procedure, surgical complications classified as Clavien 1–5, length of stay, 60-day readmission rate, and hospital costs were recorded.ResultsSeventy-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…Previous studies have found reoperation rates after colorectal resections to be higher than other general surgery procedures [1, 2, 7]. As patient outcomes and physician reimbursement are significantly impacted by reoperation rates, knowledge regarding indications for reoperation and reoperative procedures performed could provide valuable insight.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found reoperation rates after colorectal resections to be higher than other general surgery procedures [1, 2, 7]. As patient outcomes and physician reimbursement are significantly impacted by reoperation rates, knowledge regarding indications for reoperation and reoperative procedures performed could provide valuable insight.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, only 175 patients (10.2%) without wound dehiscence had a wound infection. Wound dehiscence occurred after a median (IQR) of 11 (7)(8)(9)(10)(11)(12)(13)(14)(15)(16) days and patients with wound dehiscence had a significantly higher rate of reinterventions (93% vs 6%, P < 0.001), pLOS (>11 days, 86% vs 26%; P < 0.001) and pOT (>411 min, 39% vs 25%; P = 0.03). However, the overall mortality (2.1%) and total postoperative readmission rates (6.4%) did not significantly differ ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Post-operative complications also substantially increase the use of additional resources per patient and prolong the hospital stay, raising medical costs even further. [4][5][6][7][8] A pancreatoduodenectomy (PD) is a typical example of a complex, highly specialised surgical procedure. Despite a reduction in the mortality of PD below 5% in high-volume centres, a PD is still accompanied with a substantial morbidity and post-operative complication rates are varying between 40 and 60%.…”
Section: Introductionmentioning
confidence: 99%